A STUDY OF THE FACTORS AFFECTIVE ON QUALITY OF STUDENT’S ACADEMIC PERFORMANCE IN HIGHER SECONDARY SCHOOL OF KHYBER PAKHTUNKHWA - Imran, Dr. Muhammad Imran Aziz; Khan, Dr. Umar Ali; Ayaz, Dr. Muhammad (JELM, 2025)
This descriptive study was carried out to investigate the various factors that influence student academic performance who are enroll in public secondary school of Khyber Pakhtunkhwa. The objective of the study was to investigate the various factors significantly influencing students' academic performance in Khyber Pakhtunkhwa province's higher secondary schools. There were three hundred male and three hundred female students in the 12th grade who served as respondents of the study. Because the study was quantitive in nature, the questionnaire was used to conduct a survey that gathered information on a variety of aspects of students' academic achievement. The result of the 11th class served as a tool of their academic performance. Both inferential t-test and ANOVA were utilize to check the impact of various variables of student’s achievement. The relative findings of the study showed both the parent’s education and socio-economic status (SES) had a big impact on the over[1]all student’s academic achievement as well as success in Urdu and English subjects. Performance is more impacted by socioeconomic levels that are high and average than by levels that are lower. It is quite intriguing that parents' education matters more than their line of work in terms of how well their students perform academically in higher secondary school. Finally from the results, it was resulted that female students perform better than male students.